Information Technologies in Improving Crime Prevention Mechanisms in the Border Regions of Southern Ukraine - Tamara Hubanova; Rostyslav Shchokin; Oleh Hubanov; Volodymyr Antonov; Pavlo Slobodianiuk; Sergiy Podolyaka (Nashrīyah-i mudīrīyat-i fannāvarī-i iṭṭilāʻāt, 2021)
The purpose of this study is theoretical and methodological substantiation, deepening of the conceptual provisions and development of the scientific and practical recommendations on the formation of mechanisms for crime prevention in the border regions of the southern of Ukraine. The relevance of this study is due to the need to solve the problem crime by introducing precautionary measures in the border regions of the southern of Ukraine (Bondarenko et al., 2021).The study proved the direct dependence of the level and intensity of crime on the proximity of areas to areas of significant social and criminological tension, to areas of instability and armed conflict, which contributes to the militarization of the population and increasing psychological preparedness for conflict and its antisocial methods (Iatsyshyn et al., 2020). It is established that in the border regions of the south of Ukraine the growth of criminal crime for the studied period significantly exceeds the data for Ukraine.The threats to irredentism and separatism, international terrorism, organized crime of a transnational global scale are real for the southern regions of Ukraine: economic smuggling, smuggling of weapons, ammunition and means of terror, drug trafficking, unregulated migration, trafficking in human beings and their organs.Priorities for Ukraine have been set task of crime prevention: introduction of the newest technologies of protection of a law and order, attraction of scientific and industrial potential of regions, establishment of coordination and interaction between subjects of maintenance of frontier safety at all levels (frontier, national, interstate and international) and cross-border interaction with the international organizations of fight against organized crime.Based on international experience, crime prevention measures in the border regions of southern Ukraine are proposed in the following areas: general social precautionary measures; special criminological precautions;international cooperation in the development of cross-border cooperation;introduction of automated security systems and crime prevention; informational and educational activities of formationlegal culture among the population and the public